Veterinary epidemiology and economics in Africa. A manual for use in the design and appraisal of livestock health policy - Putt, S.N.H.; Shaw, A.P.M.; Woods, A.J.; Tyler, L.; James, A.D. (International Livestock Centre for Africa, 1987)
Discusses basic techniques involved in the planning, monitoring and evaluation of livestock disease control programmes in Africa i.e. the theory & application of epidemiology statistical analysis, economics, estimating costs and decision making.